Hubungan Ruang Terbuka Hijau terhadap Penataan Ruang Bali Madya pada Rumah Tinggal - Jayadi Waisnawa; Cok. Gde Rai Padmanaba Padmanaba (Jurnal Green Growth dan Manajemen Lingkungan, 2022)
Natural disasters are commonly found in densely populated areas such as Denpasar City, Badung Regency and Gianyar. The contributing factor is the development of settlements which eliminates green open space a lot. Laws, Ministerial Regulations and Regional Regulations of the Province of Bali have not been able to control the availability of green open space. These various government efforts are in line with the concept of Bali madya traditional layout. The existence of a separate building arrangement and green open space provides space for natural ventilation and lighting to enter the interior. This study has the aim of knowing and understanding the form of green open space in residential homes with Bali madya traditional layout. This research uses descriptive qualitative method. The data were collected using a purposive sample method with the main criteria which a house that uses a traditional Bali madya layout and has green open space. From 37 residential houses, 24 houses had a temperature range of 25°C-27°C and 28 houses had cool and slightly cool air conditions. These data show that green open space in residential homes through plant and pavement elements has an important role in the interior related to natural ventilation and lighting.